2013
DOI: 10.1089/end.2012.0347
|View full text |Cite
|
Sign up to set email alerts
|

Does Imaging Modality Used for Percutaneous Renal Access Make a Difference? A Matched Case Analysis

Abstract: Objective: To assess perioperative outcomes of percutaneous nephrolithotomy (PCNL) using ultrasound or fluoroscopic guidance for percutaneous access. Methods: A prospectively collected international Clinical Research Office of the Endourological Society (CROES) database containing 5806 patients treated with PCNL was used for the study. Patients were divided into two groups based on the methods of percutaneous access: ultrasound versus fluoroscopy. Patient characteristics, operative data, and postoperative outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 16 publications
2
58
1
Order By: Relevance
“…Although statistically insignificant, the CROES study shows a lower incidence of pelvic perforation in the US group (2.9% vs 4%, p = 0.460). 20 They also reported on univariate analysis that US guidance was associated with lower postoperative hemorrhage (6% vs 13.1%, p = 0.001), although on further multivariate analysis, this difference was correlated to a larger access sheath use and multiple renal punctures ( p = 0.005, p = 0.046, respectively). 20 Additionally, the blood transfusion rate was lower in the US group (3.8% vs 11.1%, p < 0.001).…”
Section: Discussionmentioning
confidence: 94%
“…Although statistically insignificant, the CROES study shows a lower incidence of pelvic perforation in the US group (2.9% vs 4%, p = 0.460). 20 They also reported on univariate analysis that US guidance was associated with lower postoperative hemorrhage (6% vs 13.1%, p = 0.001), although on further multivariate analysis, this difference was correlated to a larger access sheath use and multiple renal punctures ( p = 0.005, p = 0.046, respectively). 20 Additionally, the blood transfusion rate was lower in the US group (3.8% vs 11.1%, p < 0.001).…”
Section: Discussionmentioning
confidence: 94%
“…During the course of the study, we were convinced that the future of PCNL access lies in 3-dimensional imaging. Authors have reported the feasibility of both ultrasound and CT guided punctures [10,11]. Until these modalities come into common use, the debate on the calyx of choice will remain relevant.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 One case-matched study comparing outcomes of ultrasoundand fluoroscopy-guided PCNL in 5806 patients found that postoperative hemorrhage and blood transfusion rates were significantly higher in the fluoroscopy group (11.1% vs 3.8%, p = 0.001), although they noted the use of larger access sheaths in the fluoroscopy group (22.6F vs 29.5F, p < -0.001) and longer hospital stays in the ultrasound group (5.3 vs 3.5 days, p < 0.001). 10 Utilizing ultrasound to achieve percutaneous renal access for PCNL has been established as safe and effective, with excellent clinical outcomes. Used in combination, ultrasound and fluoroscopy during PCNL can achieve comparable clinical outcomes and stone-free rates relative to fluoroscopy alone.…”
Section: Role In Urologic Practicementioning
confidence: 99%